Kesiapsiagaan Siswa Kelas Viii Terhadap Bencana Banjir di SMP N 2 Grogol Kecamatan Grogolka Bupaten Sukoharjo - ANDIKA, Gesit Febi (2016)
Grogol is a district that passed the Bengawan Solo river. Grogol is an average altitude of 80 m above sea level (DPL). SMP N 2 Grogol is located in the Village Sanggrahan, Grogol, Sukoharjo. Location of astronomical SMP N 2 Grogol - 7.590656 110.800378 LS and BT, the location of schools within 3.1 km of the Bengawan Solo river. This study aims to: 1) Determine the class VIII student preparedness against floods in SMP N 2 Grogol. 2) Determine the risk of flooding in Grogol. The study was conducted using a descriptive-quantitative approach, the population in the study were students of class VIII vulnerable to the threat of floods in school. Samples were taken 90 students of class VIII (F, G, H). The results of the study average value of the index preparedness eighth grade students from the tabulation of data is 63.6. The total number of respondents 90 students. The largest percentage of the data breakdowns are 55-64 percentage index value of 47.8% in the category is almost ready. From the description of data flooding risk in Grogol subdistrict menunjukakkan flood hazard evoked with 12 scores include all dikecamatan Grogol village, to the vulnerability score of 2.9 is Banaran Cemani, Sanggrahan, Manang, Kwarasan Kadokan, Grogol, Madegondo, Gedangan, and Langenharjo, whereas Telukan village, cottage, Parangjoro and Pandeyan score 3. Capacity arising from a flood with a score of 1 reach all villages in Grogol subdistrict. So based on the exposure data that has been discussed for the risk of flooding are in high positions are Desa Telukan, cottage, Parangjoro, and Pandeyan, while Banaran Cemani, Sanggrahan, Manang, Kwarasan Kadokan, Grogol, Madegondo, Gedangan, and Langenharjo flooding risk being .Kesimpulan: 1) preparedness eighth grade students to the floods in SMP N 2 Grogol in the category is almost ready with a percentage of preparedness index value of 47.8%. 2) Risk of flooding in Grogol showing 10 villages have a moderate risk with a score of 34.8 is Pandeyan, Banaran, Cemani, Sanggrahan, Manang, Kwarasan Kadokan, Grogol, Madegondo, Gedangan, and Langenharjo. High flooding risk is at 4 villages namely Telukan, cottage, Parangjoro, and Pandeyan with a score of 36.